2023
DOI: 10.1093/schbul/sbad026
|View full text |Cite|
|
Sign up to set email alerts
|

Multiomics Analyses Reveal Microbiome–Gut–Brain Crosstalk Centered on Aberrant Gamma-Aminobutyric Acid and Tryptophan Metabolism in Drug-Naïve Patients with First-Episode Schizophrenia

Abstract: Background and Hypothesis Schizophrenia (SCZ) is associated with complex crosstalk between the gut microbiota and host metabolism, but the underlying mechanism remains elusive. Investigating the aberrant neurotransmitter processes reflected by alterations identified using multiomics analysis is valuable to fully explain the pathogenesis of SCZ. Study Design We conducted an integrative analysis of multiomics data, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…However, the abundance of this ASV was negatively correlated with the acoustic startle response across all mice, suggesting that the reduced abundance of this microbe is indeed related to the SCZ phenotype. This preliminary evidence of a gut-brain relationship may mirror findings in humans, where symptom severity score was negatively correlated with the abundances of several microbes and their metabolites, including Streptococcus salivarius [36].…”
Section: Discussionsupporting
confidence: 69%
“…However, the abundance of this ASV was negatively correlated with the acoustic startle response across all mice, suggesting that the reduced abundance of this microbe is indeed related to the SCZ phenotype. This preliminary evidence of a gut-brain relationship may mirror findings in humans, where symptom severity score was negatively correlated with the abundances of several microbes and their metabolites, including Streptococcus salivarius [36].…”
Section: Discussionsupporting
confidence: 69%
“…In addition, an elevated amount of Purpureocillium was shown to be associated with more severe SCH symptomatology and poorer cognitive ability in subjects with SCH, while an elevated amount of Aspergillus was found to be associated with an improved cognitive ability. Wang et al ( 43 ) found that an altered metabolome and dysregulated microbiome were associated with neuroactive metabolites, including GABA, tryptophan and short-chain fatty acids. They underlined the association between Ruminococcus torgues and Collinsella aerofaciens and symptom intensity, and the associations between Lactobacillus ruminis and the differential metabolites, l-2,4-diaminobutyric acid and N-acetylserotonin, and cognitive ability ( 43 ).…”
Section: Gut Microbiome and Fepmentioning
confidence: 99%
“…Wang et al ( 43 ) found that an altered metabolome and dysregulated microbiome were associated with neuroactive metabolites, including GABA, tryptophan and short-chain fatty acids. They underlined the association between Ruminococcus torgues and Collinsella aerofaciens and symptom intensity, and the associations between Lactobacillus ruminis and the differential metabolites, l-2,4-diaminobutyric acid and N-acetylserotonin, and cognitive ability ( 43 ). Alterations in GABA and tryptophan neurotransmitter pathways were found to be associated with the risk of developing SCH ( 43 ).…”
Section: Gut Microbiome and Fepmentioning
confidence: 99%
See 1 more Smart Citation